PROFESSIONAL TEACHER DEVELOPMENT AS A DETERMINING FACTOR IN THE IMPROVED SCHOOL PRACTICES - Лела Б. Вуковић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2015)
Contemporary concepts in the field of professional teacher development emphasize a proactive teacher role and the dimension of individual responsibility for the process of improving one's knowledge and skills. These concepts also indicate a change in the position of teachers, from passive recipienst of the demands and challenges in the sphere of educational process, to reflexive practitioners, team workers and creators of their own paths to professional development in the context of a new educational paradigm. The purpose of this research is to offer, within a theoretical and an empirical framework, a dual approach to the professional teacher development as a determining factor in the improvement of the school practices and to indicate that the teachers' self-evalutation of their teaching competences is a key factor in their professional development. The results show that a majority of the 70 investigated secondary school vocational teachers confirm that they form their individual professional development plans based on the results of the teacher competence self-evaluation, whereas at the same time they state that the self-evaluation of competence is a determining factor of both processes, that is, of the professional teacher development and of the improved school practice.